PENINGKATKAN HASIL BELAJAR BERMAIN MUSIK ANSAMBEL DI KELAS VIII.1 SMP NEGERI 1 MUARA BUNGO DENGAN MENGGUNAKAN METODE TUTOR SEBAYA - endriani endriani (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
The problem in this study is that approximately 41% of students have not finished learning ensemble music. Limitations of lesson time / hours available in one week. There is a gap in value between students who complete the KKM and the value of students who have not completed KKM. This type of research is Class Action Research. The samples taken were 32 people. The sampling technique is done by total sampling. The technique of collecting data uses tests and observations. The results showed that learning using peer tutors had a positive impact on improving student learning outcomes. By using peer tutoring method, it can improve learning outcomes in ensemble learners on pianika musical instruments. The lowest value increases from 62 to 85 while the highest value increases from 95 to 100.